Utilização de lodo de esgoto na produção de mudas de aroeira-pimenteira - Trigueiro, Rodrigo De Menezes; Guerrini, Iraê Amaral [UNESP] (Sociedade de Investigações Florestais, 2014)
The objective of this study was to evaluate the feasibility of the sewage sludge used as substrate component for seedlings production of Brazilian pepper (Schinus terebinthifolius Raddi). The following proportions of sewage sludge/carbonized rice hull were tested, in tubes with 50 cm³: 80/20, 70/30, 60/40, 50/50 and 40/60, which were compared to a commercial substrate commonly used by forest nursery. Growth seedlings-related parameters were assessed: shoot height, collar diameter and accumulation of dry matter on the shoot and root, chemical analysis of shoot and root tissues. Schinus terebinthifolius seedlings developed in substrate with 40, 50 e 60% sewage sludge presented inferior growth compared to the control, however considering the parameters shoot height/collar diameter relation, production of dry matter on the shoot and root, and nutritional aspects, that attest to the quality of the seedlings, the results were satisfactory. Therefore, it was concluded that the use of this sewage sludge residue in the substrate composition for seedlings production of forest species is quite promising.

O objetivo deste trabalho foi avaliar a viabilidade do uso de lodo de esgoto como componente do substrato para produção de mudas de aroeira-pimenteira (Schinus terebinthifolius Raddi). Para tanto, foram testadas as seguintes proporções de lodo de esgoto/casca de arroz carbonizada, em tubetes com 50 cm³: 80/20, 70/30, 60/40, 50/50 e 40/60, as quais foram comparadas ao substrato comercial comumente usado em viveiro florestal. Foram avaliados a altura de planta, o diâmetro de colo e o acúmulo de matéria seca de parte aérea e raiz, bem como se procedeu à análise química do tecido vegetal de parte aérea e raiz. As mudas de Schinus terebinthifolius desenvolvidas em substrato com 40, 50 e 60% de lodo de esgoto apresentaram crescimento inferior ao da testemunha, entretanto, considerando os parâmetros relação altura da planta/diâmetro do colo, produção de matéria seca de parte aérea e raiz e aspectos nutricionais, que atestam a qualidade da muda, os resultados foram satisfatórios. Portanto, conclui-se que o uso do resíduo lodo de esgoto na composição de substratos para a produção de mudas de espécies florestais é uma alternativa promissora.
Use of sewage sludge for seedlings production of Brazilian pepper
Keywords: Resíduos; Substrato; Espécies Florestais; Residues; Substrate; Forest species